The study of mediation of political skill on the relationship between psychological collectivism and felt accountability through contextual and individual factors - Altuncu, Yeşim (My University, 2014)
ORTAMSAL VE BİREYSEL ETMENLERİN ETKİSİYLE PSİKOLOJİK TOPLULUKÇULUK İLE HESAP VEREBİLİRLİK ARASINDAKİ İLİŞKİNİN POLİTİK YETİ ARACILIĞIYLA İNCELENMESİ Örgüt yapısını bir arada kılan normlar ve standartlar, ortak dilin ve karşılıklı anlayışın oluşmasını sağlar. Norm ve standartların bireysel seviyede ortak bir şekilde anlaşılmasında hesap verebilirlik etkili rol oynar. Böylece, hesap verebilirlik kavramının bireysel seviyede etkileyen etmenlerin ortamsal ve bireysel etmenler ışığında araştırılması önemlidir. Bu araştırmada, psikolojik toplulukçuluk ve hesap verebilirlik ilişkisi politik yeti aracılığıyla incelenmiştir. Yapılan analizler hipotezi kısmı olarak desteklemiş, politik yetinin kısmı ara değişken rolü oynadığı saptanmıştır. Araştırmada, kültürel sıkılık-esneklik ortamsal değişken olarak alınarak, psikolojik toplulukçuluk ve politik yeti arasındaki rolü araştırılmış, fakat araştırma sonuçları şartlı değişkenden daha çok bağımsız değişken rolü oynadığını göstermiştir. Bunun yanında, değişkenler, faktörleri seviyesinde ayrıntılı incelenmiş, bireysel seviyede algılanan hesap verebilirlik kavramının birey-örgüt ilişkisi içindeki yeri araştırılmıştır. Felt accountability, psychological collectivism, political skill, cultural tightness-looseness

THE STUDY OF MEDIATION OF POLITICAL SKILL ON THE RELATIONSHIP BETWEEN PSYCHOLOGICAL COLLECTIVISM AND FELT ACCOUNTABILITY THROUGH CONTEXTUAL AND INDIVIDUAL FACTORS The consolidation of an organization through norms and standards are essential to talk a common language and create mutual understanding. Felt accountability has growing interest as a key factor to interpretation of norms and standards at individual level. So, examining the factors behind accountability at individual level framed with contextual as well as individual factors were important to demonstrate how accountability functioned in organizational dynamics. The mediation of political skill in psychological collectivism-felt accountability relation was examined in this research. Cultural tightness-looseness, as a contextual factor was proposed as a moderating variable between psychological collectivism-political skills relation. The result of the study revealed that political skill was partially mediated by psychological collectivism-felt accountability relation. Due to strong predictive power of cultural tightness over political skill, it was indicated that cultural tightness had no moderation effect in psychological collectivism-political skill relation. The findings were also discussed at factor level to demonstrate how individual-organization related by accountability.
Keywords: Örgütsel davranış; Yönetim